Effect of ArbuscularMycorrhizal Fungi (AMF) in combination with poultry manure (PM) on growth and nutrients uptake by maize - Rakiya, Abdullahi (Universiti Malaysia Sarawak(UNIMAS), 2016)
The present chemical input-intensive farming system has degraded the soil of its quality and posed some health related problems to humans. Sustainable crop production to some extent depends on the maintenance of soil quality. Applications of organic amendments and arbuscular mycorrhizal fungi (AMF) inoculum have been recommended as a good strategy to fertilize crop and improve soil quality. With the aim of reducing over dependency on chemical fertilizer, this research was conducted to isolate AMF spores and select a suitable host plant for the propagation of dominant isolates from the study area for inoculum production. The study revealed that the dominants spores were Glomus species (Gl. etunicatum, Gl. mosseae, and Gl. geosporum). In addition, Cymbopogon citratus (lemongrass) was the most suitable host for propagation of the spores compared to Allium cepa. Subsequently, a greenhouse study using sterilized soil (loam and peat) and a field trial were conducted to test the efficacy of the AM fungal inoculum in combination with varying application rates of poultry manure (PM) on the growth and nutrients uptake by maize. Effects on improvement of soil quality were also determined after maize growth. Both experiments consist of six application rates of poultry manure in tones ha-1 (0, 4, 6, 8, 10 and 12); 2 levels of AMF; inoculated (+AMF) and un-inoculated (-AMF) and recommended dose of NPK chemical fertilizer (RD NPK). AMF inoculum was a mixture of Gl. mossea, Gl. geosporum and Gl. etunicatum from trap cultures of Cymbopogoncitratus, containing spores, soil with colonized root fragments and hyphae. Results revealed that indigenous AMF inoculum has stimulated maize growth and addition of poultry manure vi has enhanced spore development and percentage of root colonization (RC %). Applying 8 and 12 tones poultry manure per hectare (t PM ha -1) in loam and peat recorded the highest root colonization %, spore density and produced maximum shoot dry biomass, comparable to RD NPK. Maximum shoot concentration for N and K (3.45 % and 2.90 %) and shoot dry biomass (25.33±0.49g) were recorded at 8 t PM ha-1 +AMF in loam with comparable values to RD NPK fertilizer (3.43 % N and 2.87 % K), (25.50±1.23 g). Applying 10 and 12 t PM ha-1+AMF was antagonistic to plant growth, nutrient uptake (N and K), and root colonization % in loam. While, 12 t PM+AMF in peat recorded shoot dry biomass (19.55±0.13 g) with high P (0.38 %) and K (2.84 %) in shoot nutrients concentration comparable to RD NPK (21.00±0.37 g), P (0.35 %) and K (2.81 %). The results also indicated that plant shoot dry biomass, nutrients uptake (N, P, and K) and root colonization percent in loam soil was significantly higher compared to peat, indicating that soil properties has significant influence on arbuscular mycorrhizal fungi effectiveness. Applying 12 t PM ha-1+AMF recorded significantly higher N (742.47 kg ha-1), P (97.51 kg ha-1) and K (576.83 kg ha-1) uptake and shoot dry biomass (199.00±3.06 g) than RD NPK in field trial. There was a strong correlation between shoot dry biomass and root colonization % in loam (R2= 0.740 P<0.01), peat (R2=0.884 P<0.01) and field study (R2= 0.753 P<0.01). Application of poultry manure with and without AMF has improved soil physical (bulk density and water-stable aggregate), chemical (pH, N-NO3, P, % OC, K) and biological properties (dehydrogenase, phosphatases and urease activities). Improvement in soil quality followed the order of PM+AMF>PM-AMF>RD NPK>Control. Results suggest that application of poultry manure and AMF could enhance maize growth by providing nutrients (N, P, and K) need of maize and improve soil quality, thus could be regarded as a reliable option for sustainable crop production.